Should our treatments be gender-specific? effect of gender on recovery from persistent post-concussion symptoms in children and adolescents participating in an active rehabilitation intervention. Issue 11 (25th May 2017) - Gagnon, Isabelle; Gauvin-Lepage, Jérôme; Friedman, Debbie; Grilli, Lisa; Kocilowicz, Helen
Abstract : Objective: To estimate the extent to which gender contributes to severity of post-concussion symptoms (PCS) in youth with concussion, who are slow to recover and who receive an active rehabilitation intervention as part of their standard care. Design: A retrospective analysis of a prospective cohort Setting: Concussion Clinic of a Paediatric Trauma Centre in Canada. Participants: 355 youth with persistent PCS (188 girls; 167 boys). All Concussion patients' information is entered prospectively in a clinical database and participants were selected for this study if they met the following criteria: 1) aged 6 to 17 years (mean=14.34, SD=2.22 years); 2) presenting with at least one PCS interfering with daily activities (mean total PCS score at initial assessment=24.50, SD=18.88), and 3) beginning an active rehabilitation intervention 4 weeks post injury (mean=30.46, SD=3.74 days). Outcome measures: Severity of post-concussion symptoms, measured by the PCS scale included in the SCAT3, was the dependent variable. PCS were assessed 3 times over a 4-week follow-up period. Main results: Boys presented with significantly less symptoms than girls 4 weeks post-injury, when starting the active rehabilitation intervention (PCSS total score mean; ♂=19.9, ♀=28.5, p<0.001, CI [−14.8, −6.4]). They continued to do so 2 and 4 weeks later, but the rate of recovery was slightly faster for girls over the follow-up period. Conclusions: Although there are gender differences in the levels of PCS 4-weeks post-injury, and while boys may recover earlier from persistent PCS, both boys and girls benefit from participating in an active rehabilitation intervention. Competing interests: None.